Discoloration induced by Raffaelea quercivora isolates in Quercus serrata logs and its relation to phylogeny: A comparison among isolates with and without the Japanese oak wilt incidence including outside of Japan - Dai Kusumoto (2018)
Japanese oak wilt (JOW) has been prevalent in Japan since the late 1980s. Infections of the fungus, Raffaelea quercivora Kubono et Shin. Ito, which is transmitted by an ambrosia beetle [Platypus quercivorus (Murayama)], can cause JOW. Although R. quercivora, P. quercivorus, and oak trees are distributed in other Asia-Pacific countries, the incidence of JOW has not been reported outside Japan. In this study, we collected R. quercivora isolates from 5 Asian countries, including Japan, and compared their ability to induce sapwood discoloration by inoculating Q. serrata logs. The tangential widths of the discoloration in sapwoods inoculated with non-Japanese isolates were equivalent to or greater than those of the 2 Japanese isolates. This indicates that a lack of JOW incidence outside Japan is not because of the lowered ability of R. quercivora to spread discoloration compared with the Japanese isolates. Statistical analyses of the relationship between discoloration and phylogeny based on DNA sequences of actin and chitin synthase showed that the discoloration width was independent of phylogenetic relatedness among the isolates. To discuss why the occurrence of JOW has not been reported outside Japan, further studies (e.g., on host susceptibility and P. quercivorus aggression) throughout Asia are needed. © 2013 The Japanese Forest Society and Springer Japan.